Investigations of the absorption and metabolism of antioxidant flavonols / Azlina Abdul Aziz - Azlina, Abdul Aziz (2000)

(untitled)
Flavonols are polyphenols, secondary plant metabolites commonly found in plants and foods of plant origin. They have widespread biological properties in the human body. The recent discovery of their potential antioxidant activities has prompted extensive research. Flavonols particularly quercetin are potent antioxidants with higher antioxidant properties than the well known antioxidant vitamins C and E. Several epidemiology studies have demonstrated a strong inverse association between flavonoid intake and risk of coronary heart disease. The association with cancer is less defined with only some studies showing an inverse association and others not. In view of their potential to act as antioxidants and prevent oxidative damage-related diseases, it is important to have an understanding of their bioavailability. Indeed, information of the absorption and metabolism of individual flavonols in man is limited. Previous investigations of their absorption have shown conflicting results. It was previously speculated that flavonol glycosides were not absorbed due to their conjugation to sugar molecules and that only the aglycones were transported into the blood stream. However, recent research has detected the presence of quercetin glycosides in plasma. These findings disagree with the earlier postulation that flavonol glycosides were not absorbed. In addition to absorption, the metabolism of flavonoids is another important area of research. As yet, little firm information is available on the fate of flavonols following absorption. The aim of the present study was to conduct further research on the absorption and metabolism of flavonols and to establish the influence of flavonol structure on the extent of their absorption and metabolism. In the first study, the accumulation of flavonols in plasma and their excretion in urine was investigated after a meal of lightly fried onions. Five healthy volunteers followed a low flavonol diet for 4 days. On day 3, after an overnight fast, subjects consumed 300 g of lightly fried yellow onions containing quercetin-3,4´-diO-b-glucoside, isorhamnetin-4´-O-b-glucoside and quercetin-4´-O-b-glucoside. Blood was sampled at 0 min, 0.5, 1.0, 1.5, 2, 3, 4, 5 and 24 h after the supplement. In addition, subjects collected all their urine for 24 h following the onion supplements. Isorhamnetin-4´-O-b-glucoside, a minor flavonol in onions accumulated in plasma at higher levels than quercetin-4´-O-b-glucoside which was a major onion flavonol. The peak concentration in plasma, expressed as percentage of intake of isorhamnetin-4´-O-b-glucoside and quercetin-4´-O-b-glucoside was 10.7 ± 2.6% and 0.13 ± 0.03 %, respectively. The time taken to reach peak plasma concentration after ingesting the onions was 1.8 ± 0.7 h for isorhamnetin-4´-O-b-glucoside and 1.3 ± 0.2 h for quercetin-4´-O-b-glucoside. Excretion in urine, as a proportion of intake, was 17.4 ± 8.3% for isorhamnetin-4´-O-b-glucoside and 0.2 ± 0.1% for quercetin-4´-O-b-glucoside. It was concluded that flavonols are absorbed into the bloodstream as glucosides. Structural differences in the flavonol molecule appeared to affect the level of accumulation and the extent to which they are excreted. Further studies investigated the influence of structural modifications on flavonol absorption from the intestine. An in vitro everted rat gut model was employed to assess the uptake of several flavonol glycosides as well as free quercetin. Everted rat jejunal segments (6-10 cm) were incubated at 37°C in 20 ml of Krebs buffer containing 10 mM of the test flavonols. The incubation media was continuously gassed with 95% O2 and 5% CO2. Incubation was performed for 30 min with samples taken every 5 min from the serosal side. The rate of uptake of flavonols were in the order of quercetin-3,4´-diO-b-glucoside > quercetin-3-O-b-rutinoside > quercetin-3-O-b-glucoside > quercetin-3-O-b-rhamnoside > quercetin-4´-O-b-glucoside > isorhamnetin-4´-O-b-glucoside > quercetin demonstrating the structural dependence of flavonols on their uptake across the intestinal mucosa. Quercetin glycosides and diglucosides as well as isorhamnetin-4´-O-b-glucoside were better absorbed than quercetin aglycone. Flavonol glycosides with glucose substitution at C3 or at both C3 and C4´ were better absorbed across the small intestine than those with a glucose substitution only at C4´. In the light of the differential uptake of flavonols across the intestine, the mechanism of their absorption was explored using the everted rat gut model described above. The uptake of quercetin-3-O-b-glucoside appeared to be concentration dependent with evidence of saturation observed in the concentration range of 10 mM to 500 mM. Several experiments were performed to assess the role of the sodium-glucose transport pathway (SGLT1) in flavonol transport. There was no significant difference in the rate of uptake of 10 mM quercetin-3-O-b-glucoside in the presence of 0, 1, 10, 50 and 100 mM glucose (P>0.05). Phloridzin, an inhibitor of SGLT1 did not reduce the rate of transport of 10 mM quercetin-3-O-b-glucoside at concentration of 1 mM and 5 mM (P>0.05) although the same concentration inhibited glucose transport by ca. 33%. A slight inhibition was observed in the uptake of 10 mM quercetin-3,4´-diO-b-glucoside in the presence of 1 mM phloridzin, but this was not statistically significant (P>0.05). The possibility of quercetin-3-O-b-glucoside acting as an inhibitor of SGLT1 was also investigated. This glucoside did not inhibit uptake of 10 mM glucose at concentrations of 10 mM, 50 mM and 500 mM. This study showed that the intestinal uptake of quercetin-3-O-b-glucoside and possibly other quercetin glucosides was carrier-mediated. We conclude from this study that SGLT1 did not play a role in the uptake of flavonol glucosides. The liver metabolism of flavonol glucosides, quercetin-3,4´-diO-b-glucoside, quercetin-4´-O-b-glucoside, quercetin-3-O-b-glucoside and isorhamnetin-4´-O-b-glucoside was investigated in an in vitro experiment. A 24 nM solution of flavonol was incubated in 10 ml of phosphate buffer (50 mM, pH 7.4, containing 10 mM MgCl2) together with 1 g of rat liver homogenates with or without 24 nM S-adenosyl methionine. Incubation was performed for 2 h at 37°C with samples withdrawn every 10 min for the first half an hour followed by every 30 min thereafter. Metabolism of the four flavonol glucosides was seen. The extent of the reaction was highest for quercetin-4´-O-b-glucoside (89.1 ± 1.7 %), followed by quercetin-3-O-b-glucoside (67.6 ± 2.7 %), isorhamnetin-4´-O-b-glucoside (63.6 ± 0.4 %) and quercetin-3,4´-diO-b-glucoside (31.9 ± 4.1 %). Extensive methylation of quercetin-3-O-b-glucoside occurred with less than 10 % remaining after 2 h. Deglycosylation of the flavonol glycosides occurred, evident from the appearance of deglycosylation products. As the percentage accumulation of metabolites was much lower than the percentage of the substrate metabolised, other metabolic reactions, in addition to deglycosylation and methylation, would appear to have been taking place. Results obtained from this thesis can partially explain the seemingly low absorption of flavonol glycosides from the small intestine and their accumulation in plasma. The structure of flavonols, particularly the nature and position of the sugar moiety, has a major influence on their absorption and potential bioavailability. Furthermore, the substantial metabolism of flavonol glucosides by the liver may contribute to the low levels of the parent compounds detected in plasma and urine. Findings from this present study raised interesting health promotion possibilities as identification of the flavonol conjugates which will be highly absorbed into the bloodstream can be used to encourage the public to increase their intakes of flavonol-rich fruit and vegetables. Identification of the metabolites of flavonol metabolism with potential antioxidant activities can further contribute towards promoting the beneficial effects of increasing intakes of flavonol-rich foods.